Hypoglycemic and High Dosage Effects of Bidens pilosa in Type-1 Diabetes Mellitus - Ajagun-Ogunleye, Mulkah O.; Tirwomwe, Michael; Mitak, Ruth Nyaboke; Kasozi, Keneth Iceland; Mbiydzenyuy, Elvis Ngala (Journal of Diabetes Mellitus, 2015)
Ethno-pharmaceutical products have received a lot of international attention in the scientific com- munity in the management of diabetes mellitus (DM). In this study we determined the anti-dia- betic and high dosage effects of Bidens pliosa in type 1 DM (T1DM). Methodology: Thirty rats were divided into six groups and subgrouped into the extract and non extract treatment groups. The extract treated group was subdivided into three groups which received 200 mg/kg, 400 mg/ kg and 800 mg/kg dosage treatments respectively. The blood glucose levels were monitored using a standard glucometer for one month, and biochemical analysis of the two liver function enzymes; Alanine aminotransferase (ALT) and Aspartate aminotransferase (AST) were carried out at the Institute of Biomedical Research (IBR-KIU-WC) at the end of week IV. The study revealed that Bidens pilosa maintained hypoglycemia for a period of two weeks and this status was lost in subsequent weeks. T1DM rats treated with a dosage of 200 mg/kg showed a better recovery (355.25 - 164.5 mg/dl) of the glucose levels, followed by those that were being treated at 400 mg/kg. The AST and ALT enzymes in blood varied with a mean ± SEM (33.72 ± 32.32 to −7.23 ± 12.61 IU and 22.98 ± 11.12 to 42 ± 38.2 IU, respectively) in both the glibencimide® and in the 800 mg/ kg treatment groups in the study. High dosages of extract were associated (P = 0.049) with increased systemic enzyme leakage. In conclusion, tissue degeneration caused by high levels of the extract was accompanied by leakage of various enzymes (AST and ALT) into the blood, which could be a major etiological factor for the development of secondary systemic pathologies, thus potentially worsening the effects of an existing T1DM prognosis in human patients. The preliminary results indicate that a dose of Bidens pilosa has an anti-diabetic effect for a limited initial duration before starting to cause systemic toxicological effects. It is highly recommended that further investigation into the cellular mechanisms and consequences of any therapy involving Bidens pilosa be carried out.
Keywords: Type 1 Diabetes Mellitus, Bidens pilosa and Diabetes, Ethno-Pharmaceutical Medicine in Uganda, Sub-Saharan Africa and Diabetes